Effect of carbohydrate mouth rinse on resistance exercise performance - Green, M. S.; Kimmel, C. S.; Martin, T. D.; Mouser, J. G.; Brune, M. P. (The Journal of Strength and Conditioning Research, 2022)
A carbohydrate mouth rinse (CMR) has been shown to enhance short duration endurance performance and raises the possibility that a similar strategy could improve performance during resistance exercise. Eighteen male and female (N = 36) resistance trained subjects (mean values ± SD; age: 21.5 ± 1.6 years, height: 1.72 ± 0.09 m, body mass: 72.8 ± 13.4 kg, and body fat: 16.7 ± 5.8%) performed 3 experimental visits during which bench press resistance exercise (4 × 10 repetitions at 65% of 1 repetition maximum [1RM] with 120 seconds recovery) and repetitions to failure at 60% 1RM were performed. Subjects rinsed 25 ml of water (WAT), noncaloric placebo (PLA), or 6.4% maltodextrin (CHO) solution for 10 seconds during exercise in a crossover, counter-balanced manner. Rating of perceived exertion (RPE), pleasure-displeasure (FS), number of repetitions to fatigue (REPS), and postexercise blood glucose (GLU) and lactate (LA) were measured. Compared to WAT (17.7 ± 0.8), PLA (19.0 ± 0.7; p = 0.025), and CHO (18.7 ± 0.8; p = 0.039) treatments resulted in higher REPS, with no difference between PLA and CHO treatments (p = 0.310). Rating of perceived exertion progressively increased each set (p < 0.0001), but was not affected by treatment (p = 0.897). Pleasure-displeasure declined during recovery from sets 3 and 4 (p < 0.05) but was also not affected by treatment (p = 0.692). Postexercise GLU (p = 0.103) and LA (p = 0.620) were not different between treatments. Although a placebo effect was present for REPS, this study failed to detect an effect of CMR on REPS, RPE, FS, GLU, or LA on upper-body resistance exercise.